Heat Fluxes and River Energy Budget on the Example of Lowland Świder River - Łaszewski, Maksym (Quaestiones Geographicae, 2015)
The paper present the energy budget of the downstream part of lowland Świder River, right tributary of the Vistula River in Mazovian Lowland, Poland. Heat fluxes were calculated on the example of four days, representing different meteorological and vegetative conditions. Results confirmed the dominant role of radiation, which accounted for an average of 90.7% and 79.7% gains and losses of thermal energy. Participation of non-radiative components proved to be far less crucial; the average contribution of condensation, sensible heat transfer, bed conduction and friction in energy gains accounted respectively to 0.0%, 0.6%, 2.9% and 5.9%, while the average contribution of evaporation, sensible heat transfer and bed conduction in energy losses reached respectively 4.5%, 1.1% and 14.6%. The results showed significant effect of riparian vegetation and cloud cover on river heat fluxes